2020
DOI: 10.3390/molecules25194578
|View full text |Cite
|
Sign up to set email alerts
|

Maillard Reaction Intermediates and Related Phytochemicals in Black Garlic Determined by EPR and HPLC Analyses

Abstract: The Maillard reaction intermediates and related phytochemicals in garlic (Allium sativum L.), which was heated for various lengths of time, using X-band (9 GHz) electron paramagnetic resonance (EPR) and high performance liquid chromatography (HPLC) were investigated. Non-spin-trap and non-destructive EPR detected the total reaction intermediates (radicals). The g-value of the signal was 2.004. The signal with a peak-to-peak linewidth (ΔHpp) was approximately 0.67 milli Tesla (mT). The values of the intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Therefore, when the pH decreased with increasing incubation time, 5-HMF increased. This is consistent with the research of Nakagawa et al 19 , who found that the 5-HMF level of garlic heated at 70 °C increased as the number of heating days increased. In addition, extensive research reported that 5-HMF has antioxidant activity, anti-ischemic functions, and other beneficial effects on the human body 20 .…”
Section: Resultssupporting
confidence: 93%
“…Therefore, when the pH decreased with increasing incubation time, 5-HMF increased. This is consistent with the research of Nakagawa et al 19 , who found that the 5-HMF level of garlic heated at 70 °C increased as the number of heating days increased. In addition, extensive research reported that 5-HMF has antioxidant activity, anti-ischemic functions, and other beneficial effects on the human body 20 .…”
Section: Resultssupporting
confidence: 93%
“…Therefore, when the pH decreased with increasing incubation time, 5-HMF increased. This is consistent with the research of Nakagawa et al [31], who found that the 5-HMF level at the 70 °C heating of garlic increased as the number of heating days increased. However, it is noted that there was a continued increase of HMF in garlic produced at 60 °C; meanwhile, in garlic produced at 80 °C, there was a continuous decrease in HMF after week 3, possibly due to moisture content [21].…”
Section: Effect Of Processing Conditions On Bioactive Compounds Of Black Garlicsupporting
confidence: 93%
“…The typical EPR settings were as follows: microwave power, 5 mW; time constant, 0.1 s; sweep time, 4 min; magnetic field modulation, 0.32 mT; and sweep width, 10 mT. The details were described in the previous report [42].…”
Section: Epr Measurementsmentioning
confidence: 99%